ポーラー パトロール キキュウ PPB I. キキュウ システム - 西村, 純; ニシムラ, ジュン; 小玉, 正弘; コダマ, マサヒロ; 鶴田, 浩一郎; ツルタ, コウイチロウ; 福西, 浩; フクニシ, ヒロシ; Nishimura, Jun; Kodama, Masahiro; Tsuruda, Koichiro; Fukunishi, Hiroshi (1984)
P(論文) 極域における気球観測の重要性が高まるに伴い, 一ヵ月に及ぶ長時間気球観測計画として, ポーラー・パトロール気球が提案されるに至った。この計画においては, 気球は南極にある観測基地から放球されることになる。厳冬期および盛夏期にはそれぞれ日の出および日没がないことを利用することにより, ゼロプレッシャー気球を比較的少量のバラスト投下で一カ月程度等高度を維持することは可能であると考えられる。これまでの気象学的検討によれば, 30km高度を飛翔する場合, 冬季なら数日間, 夏季では数週間で南極大陸周縁を周回できる。航跡の緯度円からのずれは夏季の方が冬季に比べずっと少ないので, 夏季の方がこの計画の実現性は高い。さらに, 一カ月程度の観測飛翔を行うために必要な電源, データ収録用オンボードメモリー, 飛翔中のオートバラスト機構などについても実現性の検討を進めている。気球位置についてはアルゴス・システムを利用する計画である。外国所属の基地の協力を得られた場合に期待される利点についても付記する。 Because of the importance of the balloon observations in the polar region, a project, Polar Patrol Balloon, is proposed in which a balloon will be able to float and observe around Antarctica for a month. In this project, the balloons are to be launched from some bases in Antarctica where there is no sunrise in the winter and no sunset in the summer, and a zero pressure balloon can maintain its altitude for one month by dropping a small amount of ballast. A study of meteorological feasibility had been made for this project, and it was found that a period for the balloon to fly around the pole is about one week in the winter and a few weeks in the summer at an altitude of 30km. The deviation of the trajectory from a circle is smaller in the summer season. A feasibility study was also made for power supply, on board memory storing observed data, and auto-ballasting system to perform the flight of about one month. The balloon will be located by ARGOS systems during the flights. Some merits of possible international collaboration for this project are also discussed. departmental bulletin paper